Predictors of early re-bleeding and mortality after acute variceal haemorrhage in patients with cirrhosis. Issue 6 (4th February 2008) - Bambha, K; Kim, W R; Pedersen, R; Bida, J P; Kremers, W K; Kamath, P S
Abstract : Background and aims: Risk factors for mortality and re-bleeding following acute variceal haemorrhage (AVH) are incompletely understood. The aim of this study was to determine risk factors for 6-week mortality, and re-bleeding within 5 days in patients with cirrhosis and AVH. Methods: Kaplan–Meier and Cox proportional hazards regression analyses were used to determine risk factors among 256 patients with AVH entered into a randomised, prospective trial. Results: Thirty-five patients (14%) died within 6 weeks of AVH; 14 deaths (40%) occurred within 5 days. Only the Model for End-stage Liver Disease (MELD) score and units of packed red blood cells (PRBCs) transfused in the first 24 h were associated with 6-week mortality univariately (HR 1.11, p<0.001; HR 1.22, p<0.001) and bivariately (HR MELD = 1.10, p<0.001; HR per unit of PRBCs transfused = 1.15, p = 0.005). Re-bleeding within 5 days occurred in 37 patients (15%); MELD score (p = 0.01) and a clot on a varix (p = 0.05) predicted re-bleeding. Patients with a MELD score ⩾18; both MELD score ⩾18 and ⩾4 units of PRBCs transfused; both MELD score ⩾18 and active bleeding at index endoscopy; and variceal re-bleeding had increased risk of death 6 weeks post-AVH (HR = 7.4, p<0.001; 11.3, p<0.001; 9.9, p<0.001; 10.2, p<0.001 respectively). Conclusions: Patients with AVH and MELD score ⩾18, requiring ⩾4 units of PRBCs within the first 24 h or with active bleeding at endoscopy are at increased risk of dying within 6 weeks. MELD score ⩾18 is also a strong predictor of variceal re-bleeding within the first 5 days.